Transitioning from Health Disparities to a Health Equity Research Agenda: The Time Is Now - Srinivasan, Shobha (Association of Schools of Public Health, 2014)
Health disparities are real. The evidence base is large and irrefutable. As such, the time is now to shift the research emphasis away from solely documenting the pervasiveness of the health disparities problem and begin focusing on health equity, the highest level of health possible. The focus on health equity research will require investigators to propose projects that develop and evaluate evidence-based solutions to health differences that are driven largely by social, economic, and environmental factors. This article highlights ongoing research and programmatic efforts underway at the National Institutes of Health that hold promise for advancing population health and improving health equity.